2016
DOI: 10.1016/j.msec.2015.08.045
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis and characterization of silver nanoparticles using Artemisia absinthium aqueous extract — A comprehensive study

Abstract: Unlike chemical synthesis, biological synthesis of nanoparticles is gaining tremendous interest, and plant extracts are preferred over other biological sources due to their ample availability and wide array of reducing metabolites. In this project, we investigated the reducing potential of aqueous extract of Artemisia absinthium L. for synthesizing silver nanoparticles (AgNPs). Optimal synthesis of AgNPs with desirable physical and biological properties was investigated using ultra violet-visible spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(89 citation statements)
references
References 29 publications
8
81
0
Order By: Relevance
“…Recently, a biological route for the synthesis of nanoparticles was proposed using different concentrations of silver nitrate from 20 to 0.62 mM mixed with an aqueous plant extract ranging from 100 to 0.79 mg/mL . In the method, 100–1000 mg of the dried leaves of Artemisia absinthium in powder form was boiled in 10 mL deionized water for 5 min.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Recently, a biological route for the synthesis of nanoparticles was proposed using different concentrations of silver nitrate from 20 to 0.62 mM mixed with an aqueous plant extract ranging from 100 to 0.79 mg/mL . In the method, 100–1000 mg of the dried leaves of Artemisia absinthium in powder form was boiled in 10 mL deionized water for 5 min.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Higher the concentration of plant extract can increase the number of secondary metabolites that act as reducing and stabilizing agents of silver salt in the reaction medium and eventually affect the molecular dynamics, protein conformations, and reaction kinetics. A very similar study was performed earlier that reported the effects of the different mixing ratios of reactants for the synthesis of AgNPs by using Artemisia absinthium [17].…”
Section: Resultsmentioning
confidence: 69%
“…100 μl of plant extract was mixed with 900 μl of AgNO 3 and the concentration of plant extract increased gradually from 100 μl to 900 μl and the concentration of silver salt was decreased gradually from 900 μl to 100 μl to record the effects of different mixing concentrations over the synthesis of silver nanoparticles. Mixtures were prepared in glass vials and incubated in an oven at 60°C for 24 h. After the end of the incubation period aliquot was taken from each vial and diluted with distilled water to record the absorbance in the range of 200-900 nm wavelength of light by using UV-Visible spectrophotometer (Shimadzu 1601, Japan) [17].…”
Section: Effects Of Mixing Of Different Ratios Of Reactants On the Symentioning
confidence: 99%
“…27 Secondary metabolites are active principles from plants and their inclusion in silver nanoparticles could potentially enhance their biological activities or help target the compounds. For example, numerous studies focused on the synthesis of AgNPs with extracts from Artemisia species 28,29 and evaluation of their antibacterial, antifungal, antioxidant and anticancer effects. 18,30,31 Artemisia is a widely spread genus including numerous medicinal and aromatic plants known to be a rich source of bioactive compounds (sesquiterpene lactones, flavonoids, phenolic acids, coumarins) with antimicrobial, anticancer and anti-inflammatory activities.…”
Section: Synthesis Of Silver Nanoparticlesmentioning
confidence: 99%
“…Augmentation of the extract concentration raises the average hydrodynamic sizes of AgNPs. 28 In the case of Pinus eldarica bark, on raising the amount of extract, the absorbance increased, and production of nanoparticles grew, but no directly proportionally, and the AgNPs size decreased. 46 The use of equal volumes of plant extract and silver salt led to comparatively smaller size and more stable nanoparticles.…”
Section: Concentration and Amount Of Plant Extractmentioning
confidence: 99%